2017
DOI: 10.1016/j.forsciint.2016.11.040
|View full text |Cite|
|
Sign up to set email alerts
|

Novel application of three-dimensional technologies in a case of dismemberment

Abstract: This case study reports the novel application of three-dimensional technologies such as micro-CT and 3D printing to the forensic investigation of a complex case of dismemberment. Micro-CT was successfully employed to virtually align severed skeletal elements found in different locations, analyse tool marks created during the dismemberment process, and virtually dissect a charred piece of evidence. High resolution 3D prints of the burnt human bone contained within were created for physical visualisation to assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…Numerous studies are to be found in the literature based on vibrational spectroscopy techniques, namely Raman (34,39,(61)(62)(63) and Fourier transform infrared (FTIR) (28,34,35,46,50,54,64), X-ray powder diffraction (XRD) (33,50,57,59,(65)(66)(67), X-ray fluorescence (XRF) (37,38,(68)(69)(70), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) (43,55,57,71), scanning electron microscopy (SEM) (15,43,57,(72)(73)(74)(75), nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) (15,76), and computational tomography (CT) (77)(78)(79).…”
Section: Methodologiesmentioning
confidence: 99%
“…Numerous studies are to be found in the literature based on vibrational spectroscopy techniques, namely Raman (34,39,(61)(62)(63) and Fourier transform infrared (FTIR) (28,34,35,46,50,54,64), X-ray powder diffraction (XRD) (33,50,57,59,(65)(66)(67), X-ray fluorescence (XRF) (37,38,(68)(69)(70), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) (43,55,57,71), scanning electron microscopy (SEM) (15,43,57,(72)(73)(74)(75), nuclear magnetic resonance (NMR) and magnetic resonance imaging (MRI) (15,76), and computational tomography (CT) (77)(78)(79).…”
Section: Methodologiesmentioning
confidence: 99%
“…Kilgus et al [12] provided caution for using mixed reality MR and Animations in courtrooms, the authors state the necessity for verifying the authenticity, fairness, and relevance of using of visualizations for courtroom display of evidence, noting that the data, methods and visualization must be valid. Virtual 3D models and physical 3D replicas have been used in courts of law as exhibits, there are high value and responsibility involved in courtroom display and several areas require clear definitions to be applied [13]. Firstly, it is important to differentiate between findings and simulated scenarios such as scene reconstructions [4].…”
Section: Courtroom Display Examinationmentioning
confidence: 99%
“…In toolmark analysis, microscopy techniques are used to measure toolmark properties on defleshed bone surfaces. Previous studies have used a wide range of experimental approaches for the study of saw marks [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The differences between these studies include; i) tissue types (human, animal and synthetic analog), ii) and whether the bone was fleshed, semi-fleshed or defleshed, iii) sawing actions (controlled actions such as using miter saw, free saw actions using an unrestricted human volunteer), iv) number of volunteers, v) range of saws tested both within and between class, vi) number of toolmarks created, vii) imaging methods applied (Digital microscopy, Scanning Electron Microscopy, Epifluorescence, stereomicroscopy, radiography), and viii) the method of analysis (e.g., correlation, regression, decision trees, classification trees and random forest classifiers).…”
Section: 1toolmark Analysismentioning
confidence: 99%
“…However, these methods; i) require that the tissue be defleshed so that the toolmarks are visible, ii) do not allow inspection of the internal or obscured parts of a toolmark, and iii) rarely allow 3-dimensional reconstruction of the toolmark. Micro-Computed Tomography (micro-CT) is a form of radiography that, unlike medical grade CT, allows for high resolution imaging (<100µm) of toolmarks [14][15][16][17][18]. As well as the practical benefits, such as non-destructive imaging, Norman et al, found that micro-CT could reveal additional toolmark properties not previously possible with microscopy techniques when imaging knife marks [19].…”
Section: Micro-ct Imagingmentioning
confidence: 99%
See 1 more Smart Citation